Studi tentang Sarana dan Prasarana Salon Kecantikan di Kota Sungai Penuh - Febrina, Eci; Hayatunnufus, Hayatunnufus; Yanita, Merita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This research is motivated by the problems related to infrastructure a lot of beauty salon business that is not in accordance with the Regulation of Minister of Health Director General of Nutrition and Maternal and Child Health Number HK.01.01 / BI.4 / 4051/2011 On Implementation Guidelines Beauty Salon. This study aims to examine more deeply about Infrastructures Beauty Salon in Sungai Penuh City. The research method is descriptive quantitative, data are obtained using Guttman scale observation guide. Analysis using the techniques and categorization percentage value. The population is all beauty salon medium classified amounted to 12 salons in the city of Sungai Penuh and the sample is classified as intermediate 7 beauty salon which provides services skin care and hair care. The results showed that the Completeness of equipment skin care equipment can be met is 70.78% with the category of Medium and Completeness of equipment hair care can be met is 70.08% with the Medium category. Completeness of facilities Building that can be filled is 58.16% to the category of Less Good, infrastructure, clean water that can be achieved is 74.6% with moderate category, infrastructure trash can was filled 83.11% with good category, infrastructure toilets that can be met 69.22% Uncategorized medium, and infrastructure safety equipment fulfilled 14.28% very poor category.Key Word : Equipment, Infrastructure, Beauty Salon Business, Sungai Penuh City